Ecocritical approaches to literature in French - Boudreau, Douglas, 1969-; Sullivan, Marnie M. (Ecocritical theory and practice., 2016)
Ecocritical Approaches to Literature in French applies the methods of ecocritical inquiry to French literature. To date, there is very little ecocritical scholarship on French-language literature and, indeed, very little on any non-Anglophone literature. This collection was created with two audiences in mind: it introduces an ecocritical perspective for readers of French literature, and it familiarizes ecocritics with literature in French. This collection will be a useful resource to scholars of French and Francophone literature, and of ecocriticism.